Agglomeration equilibria of hematite nanoparticles - Shimizu, K; Sokolov, S; Compton, R (Elsevier, 2016)
Nanoparticle agglomeration is a naturally occurring physicochemical process which is utilized for environmental remediation. Investigations of agglomeration equilibria have hitherto been challenging because of the lack of an appropriate in-situ analytical method. We investigate dynamic equilibria between individual and agglomerated hematite nanoparticles in 20 mM KCl solution at pH between 2.0 and 4.0 using the newly established particle-impact chronoamperometry. The results reveal that the electrochemical technique primarily detects individual Fe2O3 nanoparticles dissociated from the agglomerates indicative of the rapid and reversible nature of the agglomeration/dis-agglomeration process. A shift of the agglomeration equilibria towards cluster formation as pH increases from 2.0 to 4.0 is made apparent by the changes in the relative number and the size distribution of the monomeric nanoparticles detected. The work demonstrated herein opens a new way of investigating the agglomeration behavior of mineral nanoparticles in aquatic media.